The frequency of low birth weight and some related factors in Kodabandeh Township in 2019 - Manijeh Dinmohammadi; Ava Sadat Hosseini; Agha Fatemeh Hosseini; Tahereh Dehdari (Mashhad University of Medical Sciences, 2022)
Introduction: One of the major problems in the field of obstetrics and gynecology is the issue of low birth weight and its outcomes. Since knowing the determinants of low birth weight in each region can help to design the interventions to reduce it, so, the present study was conducted aimed to determine the frequency of Low Birth Weight (LBW) and some related factors in  Khodabandeh township.Methods: In this retrospective observational study, the needed information regarding demographic characteristics and history of pregnancy and childbirth of mothers were extracted from 936 records of deliveries performed in the first three months of 2019 from CIB System. Twenty-one records were excluded due to missed information. Data of 916 records was entered into SPSS statistical software (version 26) and was analyzed by Chi-square, Independent t-test and multiple logistic regression. P<0.05 was considered statistically significant.Results: According to the results, 85 infants (9.3%) had LBW. The results of logistic regression analysis showed that there was significant relationship between the LBW and gestational age (p<0.001), history of infertility (p=0.006), iron deficiency anemia (p=0.040), and urinary-genital infection (p=0.007).Conclusion: In prenatal care, treatment, follow-up and special attention to the identified factors affecting LBW is essential in Khodabandeh Township.